Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1667/0033-7587(2003)159[0471:tcmaab]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Membrane as a Biosensor of Oxidative Stress Induced by Radiation Exposure: A Multiparameter Investigation

Abstract: The role of biological membranes as a target in biological radiation damage remains unclear. The present study investigates how the biochemical and biophysical properties of a simple biological model, i.e. human erythrocyte membranes, are altered after exposure to relatively low doses of (60)Co gamma rays. Lipid peroxidation increased in the hours after radiation exposure, based on measurements of MDA and on the lipid peroxidation index after parinaric acid incorporation. Protein carbonyl content also increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 54 publications
4
53
1
Order By: Relevance
“…However, RBCs have the ability to resist such deformation and recover. Benderitter et al [32]. demonstrated that the level of lipid peroxidation increased in the hours after radiation exposure but was not observed after 3 days post-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, RBCs have the ability to resist such deformation and recover. Benderitter et al [32]. demonstrated that the level of lipid peroxidation increased in the hours after radiation exposure but was not observed after 3 days post-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…There are associated increases in mitochondrial permeability and calcium release as well as reactive oxygen species [25,29,30]. DNA, cellular membranes, and organelles are important targets of high-dose radiation [26,31,32], but their roles after exposure to low doses are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, how such radiation damage is induced at molecular level still not well understood [2]. When ionizing radiation interacts with matter it produces, in very short times (femtoseconds), a large number of ions, radicals, excited neutrals and ballistic secondary electrons with initial kinetic energies below 100 eV [3,4], which can subsequently cause both physical and chemical modification in the biological media.…”
Section: Introductionmentioning
confidence: 99%